Hanseníase dimorfa com surtos de reação hansênica e lesões viscerais - TONELLO, Cláudio (1979)
Dimorphous hanseniasis with outbreaks of hansenic reactions and visceral lesions. The paper presents the case of a patient with borderline hanseniasis. After a long period of illness, he presented an outbreak with new lesions, that showed reactional tuberculoid aspects; he later presented lesions with clinical and histological aspects of Virchowian hanseniasis. This evolutional type is compatible with the pseudoexacerbations outbreaks reported by Souza Lima. This patient also presented an Erythema Nodosum outbreak with cutaneous and visceral lesions, the latter occurring with great intensity in the liver parenchyma with clinical manifestations of icterus and hepatomegaly. The pathogenesis of the pseudo exacerbations outbreaks is discussed, also the special situation of Borderline patients, subject to neurologic injuries during the pseudoexacerbations outbreaks, and cutaneous, neurological and visceral lesions during the Erythema Nodosum Hansenicum outbreaks.